2006
DOI: 10.1111/j.1442-2042.2006.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment serum level of HER2/nue as a prognostic factor in metastatic prostate cancer patients about to undergo endocrine therapy

Abstract: Background: Overexpression of the HER2 receptor protein and amplification of the HER2 gene has been implicated in tumor development and progression, and has been associated with a poor prognosis in several types of cancer. The aim of this study was to evaluate whether pretreatment serum HER2 levels can be used to predict biochemical recurrence-free survival in prostate cancer patients about to undergo endocrine therapy. Methods:The study population consisted of 379 untreated patients with histologically diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…135 Expression of other TGF receptors, namely epidermal growth factor receptor (EGFR) and human epidermal receptor 2 (HER2/nue), may correlate with disease progression and hormone-refractory disease. 136 A recent report revealed that serum EGFR measurements increased the PSA vs alternate serum markers ML Ramírez et al PSA vs alternate serum markers ML Ramírez et al ability to predict positive biopsies, and levels were significantly associated with those of u-PAR. 43 Detection of CaP-specific genes using variations of PCR methods has identified numerous biomarkers in tissue and bodily fluids.…”
Section: Other Markersmentioning
confidence: 99%
“…135 Expression of other TGF receptors, namely epidermal growth factor receptor (EGFR) and human epidermal receptor 2 (HER2/nue), may correlate with disease progression and hormone-refractory disease. 136 A recent report revealed that serum EGFR measurements increased the PSA vs alternate serum markers ML Ramírez et al PSA vs alternate serum markers ML Ramírez et al ability to predict positive biopsies, and levels were significantly associated with those of u-PAR. 43 Detection of CaP-specific genes using variations of PCR methods has identified numerous biomarkers in tissue and bodily fluids.…”
Section: Other Markersmentioning
confidence: 99%
“…In our previous study, a high level of serum HER2/neu indicated a shorter interval until biochemical recurrence after endocrine therapy in patients with metastatic prostate cancer with a mean follow-up of 20.3 months. 5 This study extended the mean period of follow up to 30.8 months, and evaluated by both serum analysis and immunohistochemical assay. In this study, measurement of the serum HER2/neu level proved to be more useful as an indicator of biochemical recurrence after endocrine therapy in patients with metastatic prostate cancer than the expression of HER2/neu by IHC on multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, we found that a high level of pretreatment serum HER2/neu ECD protein is associated with a high risk of biochemical recurrence after endocrine therapy in patients with metastatic prostate cancer. 5 The ECD of the HER2/neu protein can be cleaved from the cell surface by matrix metalloproteases and then released into the blood. 13 The clinical or biological significance of HER2/neu ECD shedding is unknown, but it is probably attributable to the up-regulation of metalloproteases, which are involved in proteolytic cleavage of HER2/neu and have been linked to tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the establishment of new biomarkers is needed to identify high-risk patients as candidates for new (adjuvant) therapies and to find new surrogate endpoints to assess the efficacy of these treatments (1). In the past 10 years, conflicting results on HER-2/neu expression in prostate cancer were reported (2)(3)(4)(5)(6)(7)(8). Furthermore, it was proposed that Her2 and androgen receptors function synergistically in the absence of androgens (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%